2021
DOI: 10.3390/rs13061067
|View full text |Cite
|
Sign up to set email alerts
|

The Challenge of the Urban Compact Form: Three-Dimensional Index Construction and Urban Land Surface Temperature Impacts

Abstract: Cities are growing higher and denser, and understanding and constructing the compact city form is of great importance to optimize sustainable urbanization. The two-dimensional (2D) urban compact form has been widely studied by previous researchers, while the driving mechanism of three-dimensional (3D) compact morphology, which reflects the reality of the urban environment has seldom been developed. In this study, land surface temperature (LST) was retrieved by using the mono-window algorithm method based on La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 68 publications
3
7
0
1
Order By: Relevance
“…In the case investigated in this study (Babolsar and Fereydonkenar), tourism had a significant moderating effect on the LST in the tourism zones through developing green spaces that were constantly irrigated, and constructing on bare lands that were generally covered with sand. Although this study focused on the effects of the physical development of tourism instead of urban development, its results on the correlation between the land cover indices such as NDVI, MNDWI and EBBI with the LST are consistent with previous research [92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][110].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the case investigated in this study (Babolsar and Fereydonkenar), tourism had a significant moderating effect on the LST in the tourism zones through developing green spaces that were constantly irrigated, and constructing on bare lands that were generally covered with sand. Although this study focused on the effects of the physical development of tourism instead of urban development, its results on the correlation between the land cover indices such as NDVI, MNDWI and EBBI with the LST are consistent with previous research [92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][110].…”
Section: Discussionsupporting
confidence: 89%
“…This result shows that the LST has increased with increases in the area of built-up and bare lands, while increasing the area of vegetation and water bodies has reduced the LST in the study area. These particular results is in line with previous research showing the significant effect of vegetation on the LST [37,[100][101][102][103][104][105][106][107][108][109][110]. In this regard, Rahman et al [97], by modeling the spatial changes in the coastal lands and their effects on the LST characteristics, showed that physical changes due to urban development and built-up lands have a direct and significant effect on the LST, and this could pose a challenge for the residents of the studied areas in the future.…”
Section: Discussionsupporting
confidence: 88%
“…Mass transit networks should cover 60-75% of the city's planning areas Linking population densities with the quality of the transition system to achieve the highest economic and environmental operational efficiency Provide an integrated network of public transport at all levels of the citys planning and connect it to the pedestrian network Mixed-use areas usually reduce the use of cars by 5-15%, doubling the urban density reduces the distance that an individual usually travels by using the car by 25 Mechanisms: Roof planting reduces the temperature of the surrounding environment by an average of 9 degrees, as a decrease in the temperature of the internal environment of the building by one degree is equivalent to a 10% reduction in the electricity bill [4] Secondly: the characteristics of urban structure/patterns that achieve the efficiency in the energy consumption (Table 1)…”
Section: Planning Of Sustainable Urban Transition Systemmentioning
confidence: 99%
“…In Zayed City One of the urban patterns (no1) includes a high proportion of green spaces and recreational uses, which occupies 20-25% of the neighborhood reflects a high level of well-being compared to the formation and the traditional urban pattern of Egyptian cities such as (Madinaty/ Al Rehab in New Cairo/ Zayed) [25].…”
Section: Urban Characteristics Of the Most Efficient Urban Patternsmentioning
confidence: 99%
“…They have also explored the relationship between the formation and intensity of UHI and the set of urban physical variables in detail [ 37 , 38 , 39 ]. In this regard, physical variables, such as physical characteristics of the land surface, types of urban land use, urban density, the spatial pattern of building blocks, as well as the status of mixed land uses, have been studied [ 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. In addition, some other researchers have investigated the relationship between the demographic and economic variables of cities (e.g., population density, economic characteristics, and traffic congestion) and the formation, expansion, and intensity of UHI.…”
Section: Introductionmentioning
confidence: 99%